2016
DOI: 10.1007/s40258-016-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Increasing the Capacity of Physiotherapy Screening Clinics or Traditional Medical Services to Address Unmet Demand in Orthopaedic Outpatients: A Practical Application of Discrete Event Simulation with Dynamic Queuing

Abstract: Increasing OPSC capacity to manage semi- and non-urgent patients would be cost effective, improve throughput, and reduce waiting times without exceeding current surgical resources. Unlike Markov cohort modelling, microsimulation, or DES without DQ, employing DES-DQ in situations where capacity constraints predominate provides valuable additional information beyond cost effectiveness to guide resource allocation decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Another noteworthy point of DES for HEE is its allowing for “individual interaction”, which is valuable especially for models involving analyzing the effects of treatment delays due to patient competition for constrained resources [56, 57]. Standffield et al [56] conducted a cost-utility analysis using DES because of the need to consider the impact of introducing OPSC (Orthopaedic Physiotherapy Screening Clinics and Multidisciplinary Services) on patients queuing time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another noteworthy point of DES for HEE is its allowing for “individual interaction”, which is valuable especially for models involving analyzing the effects of treatment delays due to patient competition for constrained resources [56, 57]. Standffield et al [56] conducted a cost-utility analysis using DES because of the need to consider the impact of introducing OPSC (Orthopaedic Physiotherapy Screening Clinics and Multidisciplinary Services) on patients queuing time.…”
Section: Discussionmentioning
confidence: 99%
“…Standffield et al [56] conducted a cost-utility analysis using DES because of the need to consider the impact of introducing OPSC (Orthopaedic Physiotherapy Screening Clinics and Multidisciplinary Services) on patients queuing time.…”
Section: Discussionmentioning
confidence: 99%
“…Open access management options, but for many of these patients, non-surgical multidisciplinary management is the first line of care. 2 While evidence supports non-surgical interventions such as exercise and weight loss for the management of KOA, [3][4][5][6][7] individual patient responses may vary. It would be clinically and economically advantageous to identify patients with KOA at risk of a poor response to non-surgical multidisciplinary management at the initial consultation.…”
Section: Introductionmentioning
confidence: 99%
“… 8 The service employs experienced musculoskeletal physiotherapists (service leader) to assess and determine management pathways for non-urgent patients within orthopaedic specialist outpatient departments. 2 Where non-surgical management is appropriate, care provided by the service is patient centred with an emphasis on progression from supported to non-supported self-management and is multidisciplinary (as required; physiotherapy, occupational therapy, dietetics and/or psychology) to pragmatically address the mix of biopsychosocial factors potentially underlying each patient’s KOA presentation. 7 9 The retrospective audit showed that patients who reported lower knee function and higher levels of anxiety at their initial appointment within the service were at greater odds of a poor response to non-surgical multidisciplinary management.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that this cost could reduce to AU$29 for a physiotherapist‐led clinic, representing almost a 45% saving in per‐patient cost . Economic modeling has shown that increasing the capacity of a physiotherapist‐led assessment clinic in an orthopedic service would be cost effective, improve patient throughput, and reduce patient waiting times without exceeding available surgical resources .…”
Section: Introductionmentioning
confidence: 99%